PEMBERDAYAAN MASYARAKAT MELALUI PKPEK TERHADAP PENGRAJIN PEYEK DI DUSUN PELEMADU - Fitlayeni, Rinel (e-Journal Pelangi volume 6 No.1, 2013)
Existence PKPEK (Society for Research and Development of Community Economy) as one NGO aims to empower communities to improve peoples income Pelemadu after the massive earthquake that occurred in 2006. The earthquake caused many casualties both material and non materti. Upon entry there PKPEK a significant increase of the income of the people, especially artisans dent.PKPEK existence begins with a change in the views seen from the aspect of change in the business entity, to provide infrastructure needed by the community as an asset, manpower and motivation. While the obstacles faced during the process of mentoring, among others: a) capital mainly raw materials, b) the means of production, c) market and d) price.